The Role of Employee Engagement in Mediating Organizational Culture on Employee Performance - Qomari, Nurul; Yuliantini, Tine (Universitas Mercu Buana, 2024)
The aim of this research is to explore the impact of organizational culture on employee engagement, the impact of organizational culture on employee performance, the impact of employee engagement on employee performance, and the impact of employee engagement on organizational culture. The study utilized a causal research design that aligns with its objectives. The research sample consisted of 115 employees. The data analysis technique employed is SEM PLS (Structural Equation Modelling with Partial Least Squares). The results of the analysis show the impact of organizational culture on employee engagement. Organizational culture also has an impact on employee performance. Employee engagement also affects employee performance. In addition, employee engagement serves as a link between organizational culture and worker performance. These results underscore the significance of corporate culture in improving employee involvement and productivity. A robust and optimistic organizational culture leads to higher employee engagement and better performance. Employee engagement plays a crucial role in linking organizational culture with employee performance. This means that a good organizational culture can directly improve employee performance, as well as through increased employee engagement. Therefore, organizations aiming to improve employee performance should focus on developing a supportive and empowering organizational culture while promoting higher levels of engagement among employees.